Risk factors of dengue fever in an urban area in Vietnam: A case-control study - Thang Nguyen-Tien; Duy Cuong Do; Xuan Luat Le; Thi Hai Dinh; Lindeborg, M.; Hung Nguyen-Viet; Lundkvist, Å.; Grace, Delia; Lindahl, Johanna F. (Springer, 2021)
Background Dengue is a mosquito-borne flavivirus present in many metropolitan cities of tropical countries. Methods During and after the dengue season (September 2018 to January 2019), we conducted a case-control study in order to determine the risk factors for dengue fever in Hanoi city, Vietnam. 98 dengue patients and 99 patients with other acute infections, such as Hepatitis B virus infection, were recruited at Department of Infectious Disease of Bach Mai national hospital in Hanoi. Patients were interviewed using a structured questionnaire covering demographic, housing, environmental factors and knowledge, attitude, and practice on dengue prevention and control. Univariate analysis and multivariable logistic regression were used to determine the risk factors of dengue status. Results The mean score of knowledge items and practice items was only 7.9 out of total 19 points and 3.9 out of total 17 points, respectively. While the mean score of attitude items was 4.8 out of total 6 points. Multivariable logistic regression indicated that older patients had lesser risk of getting dengue infection as compared to younger adults aged 16–30, and patients living in peri-urban districts were less likely to suffer of dengue fever than patients living in central urban districts (OR = 0.31; 95% CI 0.13–0.75). This study could not find any association with occupation, water storage habit, knowledge, attitude, or practice on dengue prevention. Conclusions All patients had a relatively low level of knowledge and practice on dengue prevention and control. However, the attitude of the participants was good. We found that age group and living district were the risk factors correlated with the dengue status. Communication programs on raising dengue awareness should be repeated all year round and target particular groups of adolescents, younger adults, landlords and migrants from other provinces to improve their knowledge and encourage them to implement preventive measures against dengue fever.